OBJEK WISATA SAUNG ANGKLUNG UDJO: PENGELOLAAN DAN PELESTARIAN SENI PERTUNJUKAN DI KOTA BANDUNG - Dhira Rizkia Ramara; Resthy Nuraeni Safitri (Nawasena: Jurnal Ilmiah Pariwisata, 2024)
This study aims to describe the management and preservation of performing arts in the city of Bandung in the Saung Angklung Udjo tourist attraction. The background of this research starts from the author's desire to know how to manage tourist attractions from generation to generation and preserve performing arts in Saung Angklung Udjo. In addition, there are various kinds of performances staged such as wayang golek, helaran, traditional dance arts and traditional children's games that can invite tourists to interact. The problems found in the field include: 1) How to preserve the performing arts in Saung Angklung Udjo? (2) Why is the preservation process hereditary? (3) Why can the Saung Angklung Udjo tourist attraction attract the attention of local tourists and foreign tourists? In this study, the author uses a literature study method with an inductive approach. The results of this study show that the management of the Saung Angklung Udjo tourist attraction has an important role in social interaction. In addition, this tourist destination contains elements of cultural values so that it inspires and equips the community to maintain the existence of Sundanese culture.